2017
DOI: 10.1017/s0022377817000812
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Alfvénic turbulence by magnetic reconnection in a collisionless plasma

Abstract: We calculate the disruption scale λ D at which sheet-like structures in dynamically aligned Alfvénic turbulence are destroyed by the onset of magnetic reconnection in a low-β collisionless plasma. The scaling of λ D depends on the order of the statistics being considered, with more intense structures being disrupted at larger scales. The disruption scale for the structures that dominate the energy spectrum is4/9 , where d e is the electron inertial scale, ρ s is the ion sound scale, and L ⊥ is the outer scale … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 65 publications
(211 reference statements)
9
96
1
Order By: Relevance
“…Considering that f b correlates with all three of f c , f d and f ρ , we cannot constrain the physical mechanisms which relate to the spectral break. For instance, the observations of Vech et al (2018) which suggest that magnetic reconnection may disrupt the inertial cascade (Mallet et al 2017) at a disruption scale which has a similar scaling to the cyclotron resonant scale, if proton and electron temperatures are similar. Due to our current lack of electron temperature we have not made any attempt to distinguish the disruption scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that f b correlates with all three of f c , f d and f ρ , we cannot constrain the physical mechanisms which relate to the spectral break. For instance, the observations of Vech et al (2018) which suggest that magnetic reconnection may disrupt the inertial cascade (Mallet et al 2017) at a disruption scale which has a similar scaling to the cyclotron resonant scale, if proton and electron temperatures are similar. Due to our current lack of electron temperature we have not made any attempt to distinguish the disruption scale.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the inclusion of the Hall term in the MHD approximation has been proposed as the source of the break at scales d p k ⊥ ∼ 1 (Galtier 2006). Mallet et al (2017) and Loureiro & Boldyrev (2017) suggest that the inertial-range turbulence could generate sheet-like turbulent structures, which could be disrupted by reconnection below a disruption scale intermediate to d p and ρ p .…”
Section: Introductionmentioning
confidence: 99%
“…For example, LV99 in their Appendix C considered this possibility and concluded that tearing instability would affect negligibly their estimates for turbulent reconnection rates in the inertial range and at larger scales. Recently, however, an extensive literature has developed suggesting that reconnection in MHD turbulence must necessarily be induced by tearing instability, (see Loureiro and Boldyrev, 2017b;Boldyrev and Loureiro, 2017;Loureiro and Boldyrev, 2017a;Walker, Boldyrev, and Loureiro, 2018;Mallet, Schekochihin, and Chandran, 2017;Mallet, Schekochihin, and Chand ran, 2017;Comisso et al, 2018;Vech et al, 2018). The authors explore the subject of tearing instability and its possible modification of the properties of MHD turbulence.…”
Section: Objections To the Concept Of "Reconnection-mediated Turbumentioning
confidence: 99%
“…The rapid conversion of magnetic energy into heat and particle acceleration is often observed in astrophysical environments, typically in the form of flares, for instance in solar and stellar coronae (Priest & Forbes 2002), magnetars (Lyutikov 2006), jet and accretion disk systems (Romanova & Lovelace 1992), gamma-ray bursts (Drenkhahn & Spruit 2002), pulsar winds (Kirk & Skjaeraasen 2003) and their nebulae (Cerutti et al 2014). On macroscopic scales, magnetized astrophysical plasmas are invariably modeled by using the MHD approximation, with a finite conductivity to be employed in Ohm's law.…”
Section: Introductionmentioning
confidence: 99%